Voting the gender gap - Whitaker, Lois Duke (University of Illinois Press, 2008)
This book concentrates on the gender gap in voting--the difference in the proportion of women and men voting for the same candidate. Evident in every presidential election since 1980, this polling phenomenon reached a high of 11 percentage points in the 1996 election. The contributors discuss the history, complexity, and ways of analyzing the gender gap; the gender gap in relation to partisanship; motherhood, ethnicity, and the impact of parental status on the gender gap; and the gender gap in races involving female candidates. Voting the Gender Gap analyzes trends in voting while probing how women's political empowerment and gender affect American politics and the electoral process. _x000B__x000B_Contributors are Susan J. Carroll, Erin Cassese, Cal Clark, Janet M. Clark, M. Margaret Conway, Kathleen A. Dolan, Laurel Elder, Kathleen A. Frankovic, Steven Greene, Leonie Huddy, Mary-Kate Lizotte, Barbara Norrander, Margie Omero, and Lois Duke Whitaker._x000B_
Keywords: Börngen, ...; Women -- Political activity -- United States -- History -- 21st century.; Voting -- United States -- History -- 21st century.; Political participation -- United States -- History -- 21st century.; Women political candidates -- United States.; Sex role -- Political aspects -- United States.; United States -- Politics and government -- 21st century.; Femmes -- Activité politique -- États-Unis -- Histoire -- 21e siècle.; Vote -- États-Unis -- Histoire -- 21e siècle.; Participation politique -- États-Unis -- Histoire -- 21e siècle.; Candidates (Élections) -- États-Unis.; Rôle selon le sexe -- Aspect politique -- États-Unis.; États-Unis -- Politique et gouvernement -- 21e siècle.; POLITICAL SCIENCE -- Political Process -- Elections.; POLITICAL SCIENCE -- Political Process -- General.; SOCIAL SCIENCE -- Gender Studies.; Political participation; Politics and government; Sex role -- Political aspects; Voting; Women -- Political activity; Women political candidates; United States; Wählerin; Politikerin; Kandidatin; Geschlechterrolle; Wahl; Wahlverhalten; Frau; USA; 2000-2099; History